IMPLEMENTASI KERJA SAMA INDONESIA - AMERIKA SERIKAT MELALUI NATIONALLY DETERMINED CONTRIBUTION (NDC) DALAM MENGURANGI EMISI KARBON PERIODE 2019-2022 - Bella Anandaputri Suryandari, (2023)
Indonesia is the 5th largest country in the world as a producer of carbon dioxide gas emissions but the high carbon emissions have a negative impact on the people of Indonesia. Therefore, discussions on efforts to reduce carbon emissions must be a priority for all parties in bilateral cooperation. This study aims to discuss efforts to reduce carbon emissions through the implementation of cooperation between Indonesia and the United States through Nationally Determined Contribution (NDC) in the 2019-2022 period. This study uses a descriptive qualitative method accompanied by green politics theory, the concept of carbon emissions, and the concept of bilateral cooperation. This research departs from the idea that Indonesia needs cooperation with the United States in reducing carbon emissions to achieve the target Nationally Determined Contribution (NDC). Then, proceed with the form of cooperation Nationally Determined Contribution (NDC) period 2019-2022 so as to achieve results of cooperation Nationally Determined Contribution (NDC) period 2019-2022. The results of this study indicate that the cooperation between Indonesia and the United States through Nationally Determined Contribution (NDC) for the 2019-2022 period has been implemented well as evidenced by the existence of several programs and policies that have been implemented. This collaboration is considered important because it is to develop low-carbon development in Indonesia nationally, build a workforce through training or exchange of experts who will later have the opportunity to open jobs in Indonesia, and show a positive image in the international arena.